2011
DOI: 10.1186/1471-2458-11-357
|View full text |Cite
|
Sign up to set email alerts
|

Experience of violence and adverse reproductive health outcomes, HIV risks among mobile female sex workers in India

Abstract: BackgroundFemale sex workers (FSWs) are a population sub-group most affected by the HIV epidemic in India and elsewhere. Despite research and programmatic attention to FSWs, little is known regarding sex workers' reproductive health and HIV risk in relation to their experiences of violence. This paper therefore aims to understand the linkages between violence and the reproductive health and HIV risks among a group of mobile FSWs in India.MethodsData are drawn from a cross-sectional behavioural survey conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 31 publications
13
78
1
3
Order By: Relevance
“…Almost all the participants explained that gender-based violence increases the risk of different adverse reproductive outcomes, such as unwanted pregnancy, abortion, miscarriage, still birth, HIV/AIDS and fistula among married women. This finding is consistent with a study conducted in India, where women who were victims of genderbased violence experienced increased risks of multiple forced terminations of pregnancies 30 . The association between gender-based violence and adverse reproductive health outcomes might be that women who are physically and sexually violated have limited access to contraception which leads to unwanted pregnancies and usually ends up in abortion.…”
Section: African Journal Of Reproductive Health December 2017; 21(4):108supporting
confidence: 92%
See 1 more Smart Citation
“…Almost all the participants explained that gender-based violence increases the risk of different adverse reproductive outcomes, such as unwanted pregnancy, abortion, miscarriage, still birth, HIV/AIDS and fistula among married women. This finding is consistent with a study conducted in India, where women who were victims of genderbased violence experienced increased risks of multiple forced terminations of pregnancies 30 . The association between gender-based violence and adverse reproductive health outcomes might be that women who are physically and sexually violated have limited access to contraception which leads to unwanted pregnancies and usually ends up in abortion.…”
Section: African Journal Of Reproductive Health December 2017; 21(4):108supporting
confidence: 92%
“…This corroborates the already established link between alcohol and violence. Different studies have documented that many men who abuse alcohol have been violent to female partners and are perpetrators of domestic violence 30,32 . Almost all the participants explained that gender-based violence increases the risk of different adverse reproductive outcomes, such as unwanted pregnancy, abortion, miscarriage, still birth, HIV/AIDS and fistula among married women.…”
Section: African Journal Of Reproductive Health December 2017; 21(4):108mentioning
confidence: 99%
“…Moreover, inequitable gender norms, criminalisation and stigmatisation of sex work contribute not only to their increased risk of IPV, but also to the challenges female sex workers encounter for harm reduction, as they are less likely to seek or receive assistance from violent situations (Ratinthorn et al 2009;Beattie et al 2010;Decker et al 2010;Mbonye et al 2012;Shannon et al 2012). Female sex workers also are at increased risk for adverse reproductive health outcomes, including sexually transmitted infections and unintended pregnancies (Swain et al 2011). A recent meta-analysis of 102 articles from studies conducted in 50 countries revealed that female sex workers have much greater risk of HIV infection than women who do not engage in sex work (OR 13.5; 95% CI 10.0 -18.1) (Baral et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…These risks include violence perpetrated against sex workers, high HIV prevalence and sustained antenatal exposure to HIV and other STIs, and limited engagement in healthcare services, which may collectively have deleterious effects on pregnancy outcomes. [64][65][66][67][68] Yet, fertility-related evidence has focused predominantly on the incidence of pregnancy among sex workers and their unmet contraceptive needs. [69][70][71] Continued efforts to integrate emergency contraception into sex worker-friendly services, and measurement of the impact of these services on unsafe abortions would help to expand the evidence base.…”
Section: Resultsmentioning
confidence: 99%